The Effect of Flipped Classroom Model on Mathematical Ability: A Meta Analysis Study - Purnomo, Bagus; Muhtadi, Ali; Ramadhani, Rahmi; Manaf, Abdul; Hukom, Julham (FKIP Universitas Lampung, 2022)
The Effect Of Flipped Classroom Model On Mathematical Ability: A Meta-Analysis Study. Objective: This study aims to determine the effect of the flipped classroom model on mathematical ability. Methods: The study design was a meta-analysis by analyzing 70 effect sizes from 44 primary studies that met the inclusion criteria. Findings: The combined effect size was (d = 0.73; p < 0.01). Measure the effect based on education level (Qb = 21.04; p < 0.05), use of LMS (Qb = 5.91; p < 0.05), sample size (Qb = 9.83). ; p < 0.05), year of study (Qb = 34.85; p < 0.05), type of publication (Qb = 7.08; p < 0.05), trial period (Qb = 46.60; p < 0.05), and region (Qb = 49.59; p < 0.05). Conclusion: The flipped classroom model has an effect on mathematical ability. The effect of the flipped classroom model compared to traditional teaching on math skills differs according to the educational level group, use of LMS, sample size, year of study, type of publication, time of experiment, and region.Keywords: Mathematical ability, flipped classroom, meta-analysis.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202216